PARAMETER STUDY OF OFFSHORE PIPELINES INSTALLATION USING S-LAY METHOD IN STATIC AND DYNAMIC CONDITION CASE STUDY: 16ÃâÃâ INFIELD FLOWLINE TERANG-SIRASUN- BATUR OIL AND GAS FIELD DEVELOPMENT - ADRIPTA (NIM : 23109005); Pembimbing: Prof.Dr.Ir.Indra Nurhadi, PALKA
Mobilization of oil and gas exploration from onshore to offshore region requires special attention especially during the installation process. Some aspects need attention include stress and strain limits of design, also design appropriate safety criteria codes and standards commonly used in oil and gas industry. In this thesis conducted static and dynamic analysis of the distribution of pipe stress which occurred during the installation process is done by using S-lay method. Static and dynamic conditions are reviewed taking into account the influence of the wave during the process of pipe installed. As a case study, the authors analyze the process of installation will be done on the 16Ã‚Â” infield flowline in the Terang, Sirasun and Batur field with a depth of 130 meters by using the configuration of the Kuroshio II laybarge. Pipe stress calculation is done by Offpipe software and wave simulation is done by Moses software. The total pipe stress produced will be evaluated based on DNV-OS-F101 criteria and influence of wave motions will be evaluated based on DNV-RP-C205 criteria. Wave analysis results showed that for the influence of vortex shedding during the process of pipe installed is not significant. While the analysis of the safety criteria in the design load resistance criteria of stinger quite vulnerable and potentially unsafe conditions. Assesment of other design criteria of local buckling criteria stated collapse, local buckling and propagating buckling will not exist in the pipeline system.